2022
DOI: 10.3389/fpsyg.2022.959406
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of firm performance through corporate governance and information technology investment with mediating role of corporate social responsibility: Evidence from Saudi Arabia telecommunication sector

Abstract: This study intended to examine the effect of information technology (IT) investment and corporate governance mechanism on the performance of the Saudi telecommunication sector with mediating role of corporate social responsibility (CSR). A survey method was used to collect data from the targeted Saudi telecom firm. Results show that corporate governance practices, i.e., internal audit, internal audit committee, and internal board size, have a significant and positive relationship with firm performance. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…Thus, these banks would target low liquidity to hold consequently, greater exposure to liquidity risk. The relationship is in accordance with the theory of too big to fail (Stern & Feldman, 2004, Alfalah et al, 2022. Deari et al (2022) show a positive relationship between economic growth and liquidity risk.…”
Section: Literature Reviewsupporting
confidence: 88%
“…Thus, these banks would target low liquidity to hold consequently, greater exposure to liquidity risk. The relationship is in accordance with the theory of too big to fail (Stern & Feldman, 2004, Alfalah et al, 2022. Deari et al (2022) show a positive relationship between economic growth and liquidity risk.…”
Section: Literature Reviewsupporting
confidence: 88%
“…The findings indicated that corporate governance had a significant and positive effect on financial performance. In Saudi Arabia, Alfalah et al (2022) examined the effect of corporate governance practices on firm performance in the telecommunication sector. The results showed that the corporate governance practices, i.e., internal audit, internal audit committee, and internal board size, had significant and positive effect on firm performance.…”
Section: The Global Perspective Of Corporate Governance Mechanisms An...mentioning
confidence: 99%
“…However, corporate governance has remained extensively controversial to researchers, corporate managers, financial analyst, academicians, and strategists (Onu & Ndah, 2022). The insufficiency of existing corporate governance legislation, principles, structures, and processes to prevent these types of frauds has stoked disputes over the effectiveness of these governing mechanisms (Alfalah, Muneer, & Hussain, 2022). Corporate governance has received attention globally due to the recent corporate failure in many corporate organizations (Arenekeet al, 2022;Munyoki, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed research will analyse the changes made to the corporate governance regulations in lieu of the Enterprise performance for perceived relations (Montagu, 2015). Different studies (e.g., Alshareef et al, 2015;Alfalah et al, 2022) have been done to investigate the bond between corporate governance and company's performance in emerging and developing countries. Nevertheless, few have considered the literature on Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%